2019
DOI: 10.1007/s42399-019-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasound in the Diagnosis and Follow-Up of Transient Perivascular Inflammation of the Carotid Artery (TIPIC) Syndrome: a Case Report

Abstract: Idiopathic carotidynia (IC) is a rare, possibly under-diagnosed clinico-radiologic entity that consists of acute unilateral neck pain and tenderness over the carotid bifurcation. Lecler et al. have recently described this condition associated with characteristic imaging features of transient perivascular soft tissue inflammation at the level of the affected carotid bifurcation, by a new term TIPIC (transient perivascular inflammation of the carotid artery) syndrome. We report the case of an Indian man, with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, it has been an inconsistent finding across the literature. The role of US in follow-up of patients with TIPIC syndrome has been documented by the above mentioned authors [1,6,7,9].…”
Section: Minor Criterionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, it has been an inconsistent finding across the literature. The role of US in follow-up of patients with TIPIC syndrome has been documented by the above mentioned authors [1,6,7,9].…”
Section: Minor Criterionmentioning
confidence: 92%
“…Takamura et al have reported a rare recurrent case of TIPIC syndrome with a temporary carotid plaque in a young male[6]. I have encountered and reported a case of recurrent unilateral TIPIC syndrome with a past history of transient symptoms on the contralateral side of the neck[9]. Imaging techniques such as ultrasound (US), magnetic resonance imaging (MRI), computed tomography (CT) imaging, CT angiography (CTA), and [18F] fluoro-deoxy-glucose positron-emission tomography-CT have been employed for establishing the diagnosis of this benign, self-limiting condition[1,10].In 2005, Arning reported a consistently similar ultrasound pattern of hypoechoic perivascular soft tissue thickening along the carotid bulb, exactly in the region of tenderness along with slight narrowing of the affected vessel lumen; in six patients suspected of carotidynia[11].…”
mentioning
confidence: 99%